Growth regression models at two generations of selected populations Alabio ducks - Triana Susanti; L Hardi Prasetyo (Jurnal Ilmu Ternak dan Veteriner, 2007)
A selection process to increase egg production of Alabio ducks was conducted in Balai Penelitian Ternak, Ciawi-Bogor. The selection aimed at increasing production, however observation on growth of the selected ducks was necessary since early growth stage (0-8 wks) determines the performance during laying period. This paper presents the growth models and the coefficient of determination of two generations of selected Alabio ducks. Body weight were observed weekly on 363 ducks from F1 and 356 ducks from F2, between 0-8 weeks and then fortinghly until 16 weeks. Growth curves were analysed using regression models between age and bodyweight of each population. The selection of model with the best fit was based on the large value of determination coefficient (R2), small value of MSE, and sinificant level of regression coefficient. Result showed that cubic polynomial regression was the best fit for the two populations, Y = 56.31-1.44X+0.64X2-0.005X3 for F1 and Y = 43.05 + 0.96X + 0.69X2 - 0.0056X3 for F2. The values of R2 were 0.9466 for F1 and 0.9243 for F2, and the values of MSE were 11.586 for F1 and 19.978 for F2. The growth of F1 is better during starter period, but F2 is better during grower period. Key Words: Regresion, Growth, Alabio Duck